Analysis of Mispronunciation The "TH" Sound by EFL Learners in University Level - Adhelya Putri Dyani; Naafa Nabiila Romadhoni; Wahyu Indah Mala Rohmana (PRASASTI: Journal of Linguistics, 2025)
This study aims to analyze the pattern of pronunciation errors of "TH" (/θ/ and /ð/) by EFL (English as a Foreign Language) students at the university level. This study used a qualitative research method with pronunciation test instruments and semi-structured interviews. The results showed that EFL students in Indonesia have difficulty in pronouncing the "TH" sound due to the influence of their mother tongue (L1) which does not have the same sound. Students tend to replace the "TH" sound with other sounds such as /t/, /d/, or /s/, depending on the position of the "TH" sound in the word. Interviews with students also showed that psychological and social factors such as shyness and fear of being judged also affect the pronunciation errors of the "TH" sound. This study emphasizes the importance of considering the influence of the mother tongue and psychological factors in teaching English pronunciation.